Analisa Perbandingan Kekuatan Profil Padeye Berdasarkan Desain Standara DNV dan BS-EN Studi Kasus: Cargo Carrying Unit - Feri Noviantoro; Indraswari Kusumaningtyas (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2021)
Abaqus Manual Book Version 6.8 (2008) – Getting started with Abaqus (Interactive Edition)ASTM A36/A36M - 14 (2015) – Standard Specification for Carbon Structural SteelBS EN 12079-1:2006 – Offshore containers and associated lifting sets — Part 1: Offshore containers — Design, manufacture and marking.BS EN 12079-2:2006 – Offshore containers and associated lifting sets — Part 2: Lifting sets — Design, manufacture and marking.BY Y. HIGASHIDA, J. D. BURK, AND F. V. LAWRENCE, JR. (1978). StrainControlled Fatigue Behavior of ASTM A36 and A514 Grade F Steels and 5083-0 Aluminum Weld Materials.Bukaka. (2010). Provision of Cargo Carrying Unit Project.Chevron. (2009). MCA – Lifting and Rigging Standard. Houston: Chevron Corporation.Crosby Catalogue (2003) – Crosby Bolt-Type ShacklesDaniela Scorza, Andrea Carpinteri, Sabrina Vantadori (2018). Tension failure assessment at lug hole edges. Department of Engineering & Architecture, University of Parma.DNV No. 2.7-1 2013 – Standard for Certification of Offshore Containers.Gérald Portemont, Julien Berthe, Alain Deudon, François-Xavier Irisarri (2018). Static and dynamic bearing failure of carbon/epoxy composite joints. DMAS, ONERA, University Paris Saclay.Henny Gusti Pramita, Handayanu dan Yoyok Setyo H. (2013). Analisis Struktur Padeye pada Proses Lifting Jacket Empat Kaki dengan Pendekatan Dinamik. Jurusan Teknik Kelautan, Fakultas Teknologi Kelautan, Institut Teknologi Sepuluh Nopember (ITS).Hikmat Saaid Saleh (2016). Ultimate capacity of pad eyes in lifting operations. Faculty of Science and Technology, University of Stavanger.Hoover Ferguson Group, Inc (2018) – Definition of Cargo Carrying UnitsIqbal Gayuh R.M.S, Yeyes M, dan Yoyok S.M. (2016). Analisis Keandalan Struktur Padeye Berdasarkan Konfigurasi Rigging pada Lifting Upper Deck Modul MODEC dengan Pendekatan Dinamik. Jurusan Teknik Kelautan, Fakultas Teknologi Kelautan, Institut Teknologi Sepuluh Nopember (ITS).Roberto Leon. (2018). Journal of Visualized Experiments, Stress-Strain Characteristics of Steels. Department of Civil and Environmental Engineering, Virginia Tech, Blacksburg, VAT.W. Ling, X.L. Zhao, R. Al-Mahaidi, J.A. Packer (2006). Investigation of block shear tear-out failure in gusset-plate welded connections in structural steel hollow sections and very high strength tubes. Civil Engineerng, Faculty of Civil Engineering, Monash University.